Tenofovir Disoproxil Fumarate/Emtricitabine and Baricitinib for Patients at High Risk of Severe Coronavirus Disease 2019: The PANCOVID Randomized Clinical Trial. (20th August 2022) - Montejano, Rocío; de la Calle-Prieto, Fernando; Velasco, María; Guijarro, Carlos; Queiruga-Parada, Javier; Jiménez-González, María; González-Ruano, Patricia; Martínez, Patricia; Goikoetxea, Ane Josune; Ibarrola, Marta; Ciudad, Marianela; Gutiérrez, Ángela; et al.
Abstract: Background: This study was designed to evaluate if patients with high risk for severe coronavirus disease 2019 (COVID-19) would benefit from treatment with tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) followed by baricitinib in case of hypoxemia and systemic inflammation. Methods: PANCOVID is an open-label, double-randomized, phase 3 pragmatic clinical trial including adults with symptomatic COVID-19 with ≥2 comorbidities or aged ≥60 years and was conducted between 10 October 2020 and 23 September 2021. In the first randomization, patients received TDF/FTC or no TDF/FTC. In the second randomization, patients with room air oxygen saturation <95% and at least 1 increased inflammatory biomarker received baricitinib plus dexamethasone or dexamethasone alone. The primary endpoint was 28-day mortality. Main secondary endpoint was 28-day disease progression or critical care unit admission or mortality. The trial was stopped before reaching planned sample size due to the decrease in the number of cases and a mortality rate substantially lower than expected. Results: Of the 355 included participants, 97% were hospitalized at baseline. Overall, 28-day mortality was 3.1%. The 28-day mortality relative risk (RR) for participants treated with TDF/FTC was 1.76 (95% confidence interval [CI], .52–5.91; P = .379); it was 0.42 (95% CI, .11–1.59; P = .201) for those treated with baricitinib. The 28-day RR for the main secondary combined endpoint for participants treated with TDF/FTC was 0.95 (95% CI, .66–1.40; P = .774); it was 0.90 (95% CI, .61–1.33; P = .687) for those treated with baricitinib. Conclusions: Our results do not suggest a beneficial effect of TDF/FTC; nevertheless, they are compatible with the beneficial effect of baricitinib already established by other clinical trials. Clinical Trials Registration: EudraCT: 2020-001156-18. Abstract : The PANCOVID clinical trial does not suggest a beneficial effect of tenofovir disoproxil fumarate/emtricitabine for mainly hospitalized patients at high risk of severe COVID-19. Our results are compatible with the beneficial effect of baricitinib already established by prior clinical trials.